Cure retardation of peroxide-cured silica filled natural rubber influenced by organosilane - Sirichai Pattanawanidchai (2020)
© 2018 Society of Plastics Engineers The influence of silane coupling agent on properties of silica-filled compounds under peroxide curing was investigated. bis (triethoxysilylpropyl) tetrasulfide (TESPT) was selected in this study and its content was varied from 0 to 12% w/w of silica. It is found that with increasing TESPT content, bound rubber content, tensile strength, elongation at break and tear strength are enhanced. By contrast, magnitude of Payne's effect, modulus at 100% elongation (M100) and heat build-up are decreased. The changes of such properties are attributed to the reduction of crosslink density in conjunction with the improvements of both rubber–filler interaction and degree of filler dispersion with increasing TESPT content in the peroxide curing system. POLYM. ENG. SCI., 59:42–48, 2019. © 2018 Society of Plastics Engineers.